Analysts' disagreement and investor decisions - Wolfgang Gick; Alex Weissensteiner (Research Institute of Industrial Economics (IFN), 2018)
Earning forecasts disclosed by financial analysts are known to be overly optimistic. Since an investor relies on their expertise, the question arises whether he would take analyst recommendations at face value or instead structure consultation with differently upward-biased analysts in a way that would permit him to make more accurate investment decisions. We characterize disagreement in a strategic disclosure game where two analysts disclose to an investor who has commitment power. This setup delivers an explanation of why "de-biasing" occurs naturally when disagreement carries through the disclosure process itself. Our results suggest that consulting more than one analyst permits the investor to make more accurate decisions, even if both analysts overstate their recommendations. We generalize our findings to the case of noisy observation.
Keywords: G11; G14; G17; D83; 330; Strategic Information Transmission; Disagreement; Upward-biased Experts; Commitment Power; Noisy Observation